BACTERIAL VAGINOSIS IS A DANGEROUS DISEASE (Modern education and development, 2024)
Bacterial vaginosis (BV) is a disorder of the vaginal microflora that occurs when the normal microbiota is replaced by high concentrations of anaerobic bacteria.  Statistics from various authors show that 40–50% of all cases of the appearance or change of vaginal discharge are caused by bacterial vaginosis and approximately 25 to 50% of women today suffer from this disease [1–5].